Data Insights: Menerapkan Analisis Deskriptif dan Semantik Diferensial menggunakan Microsoft Excel - Mochamad Wartaka; Sumardjono; Dimas Ari Darmantyo; Dadang Junaedi; Dadi Muhamad Hasan Basri; Dede Suparman; Hery Siswanto; Wartoyo Hadi (LP3M Universitas Binaniaga Indonesia, 2025)
The purpose of this Community Service activity is to enhance participants' understanding of the basic concepts of data analysis and its application in research, equip participants with practical skills in using Microsoft Excel to process and analyze data, and assist participants in presenting data analysis results effectively and attractively. This training method includes three different methodologies: presentation method, demonstration method, and practice method. The results of this activity showed that participants were able to create visualizations of descriptive data analysis in the form of attractive and easy-to-understand graphs, making the presented information easier for readers to digest. Participants were then invited to practice creating graphs using the provided dataset with Ms Excel, allowing them to directly experience the benefits of the techniques taught. The graphs created were multi-series graphs to display all the data, and 3D graphs to display each individual data point. The training conducted was able to enhance students' knowledge and skills in using Microsoft Excel for data processing and visual presentation of descriptive analysis.